A prospective study on causes and functional outcome of frozen shoulder - Mahajan, Sanjeev; Gadi, Daksh; Gupta, Rahul; Singla, Saurav; Setia, Piyush; Gupta, Som; Kaur, Raminder (International Journal of Medicine, 2016)
Backgroud: Frozen shoulder also called as adhesive capsulitis is a condition characterised by global limitation of humeroscapular motion resulting from contracture and loss of compliance of the glenohumeral joint capsule. Frozen shoulder is a common problem and results in frustrating debilitation for its sufferers. There can be many reasons for pain and stiffness of shoulder joint, so it is very important to differentiate between adhesive capsulitis and the other causes.Objective: The main objective of the study was to evaluate the various modes of treatment for frozen shoulder and to identify various causes and associations of frozen shoulder in Indian population. To the best of our knowledge no prospective study has been done which have compared different treatment options in patients of adhesive capsulitis in Indian population.Methods: The study was done on 75 patients which were divided into three groups, based on the mode of management i.e. conservatively with medication and physiotherapy, physiotherapy and intraarticular injection and arthroscopic capsular release. The range of movement and functional outcome was compared using Constant & Murley score.Conclusion: We found that patients undergoing conservative management showed benefits of various treatment options if the condition is diagnosed at an early stage but the results convincingly prove the advantages of arthroscopic capsular release in patients with chronic painful stiff shoulder or in failed conservative treatment.